USING WORD REDUCTIONS AND ASSIMILATION IN SPEAKING ENGLISH - Davronov Doston (Journal of new century innovations, 2022)
When you're learning English as a second language, you tend to pay more attention to how you say each word. This is why you talk slower than people who speak English as their first language. Americans, on the other hand, don't have to pay extra attention to how they say words because they speak English naturally, which includes useful speech techniques like reduction. Some ways that spoken English is different from written English make Americans sound different when they talk. Since pronunciation is part of speaking, there are ways to improve your pronunciation that every American knows and uses to speak more easily and quickly. Reduction is one of these ways.